IMPROVING READING COMPREHENSION OF SENIOR HIGH SCHOOL STUDENTS THROUGH SCANNING AND SKIMMING TECHNIQUES - Rahmawati, Rahmawati (Universitas Borneo Tarakan, 2019)
The purpose of this research was to find out the students reading comprehension improvement through scanning and skimming techniques for students in SMA Muhammadiyah Tarakan. This research was quasi experiment. In this research, the researcher used two class. The researcher compared control class and experiment class whether there was any difference and improvement before and after giving treatment. The control class was given by skipping and paraphrasing techniques, meanwhile experiment class was given by scanning and skimming techniques. The subject of this study were XI IIS 3 as the experiment class there were 27 students and XI IIS 2 as the control class there were 26 students. The instruments were reading test that included pretest and posttest. Besides that, the researcher used descriptive analysis to analyze the data and SPSS veersion 22.0 for inferential analysis. The result of this research indicated that there were differences between pretest and posttest in both of the class. It was proven by the result of the students mean score. The students mean score in experiment class of pretest was 47,59 and posttest was 63,70. On the other hand, the students mean score in control class of pretest was 55,19 and posttest was 60,00. It can be seen from both of the class were have improvement. Eventhough, the treatment was different, but the comparison between control and experiment class, the experiment class was got higher improvement after giving the treatment by using scanning and skimming techniques, ratherthan the control class that was given by using skipping and paraphrasing techniques. It means that in experiment class the improvement of the students mean score was 16,11 point. The result of independent sample Ttest in posttest showed that Ttest (1,707) higher than Ttable (1,675). The result of this research there was the students reading comprehension was improve after using scanning and skimming techniques. Then it can be concluded that scanning and skimming can improve the students reading comprehension for studnts in SMA Muhammadiyah Tarakan.